(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
Insecticide resistance monitoring of mosquito field populations is a crucial for guide and select the rational application of this insecticide. Both, levels and mechanisms of resistance are important to select effi cient insecticides for the control of disease vectors. Culex pipiens mos quitoes collected from three different Governorates in Egypt (El-Fayoum, Menofia and Giza), were tested for insecticides susceptibility against Lambda-cyhalothrin and DDT. The results showed high resistance to the tested insecticides among Menofia and Giza collected populations, whereas El-Fayoum population showed low level of resistance. a great precaution should be considered about the type of control measures in these areas, when using the same insecticide. The presented output is alarming to health sectors and vector control decision makers. Mosquito control programs may need considering alternative insecticide classes for control of C. pipiens in the monitored areas.